التخفبف بالتسكين في كتاب سيبويه (مجلة الواحات للبحوث والدراسات, 2017)
Elision Is A Phenomenon That Identifies  The Arabic Language In Its Voices, Words And Structure .Arabs Tend To Sum Up If Felt That They Can Do Without  Some Parts Of Speech. And It Is Not Allowable To Elide Unless The Recipient Understands The Meaning Of The Words Clearly, Because If The Language Is Blurred, The Recipient Does Not Understand What Is Being Said To Him, And Thus It Does Not Lead To Effective Communication Between People.The Omission Of Sounds Is Considered One Of The Most Important Tools Used By Arabs To Reduce The Value Of Words. They Deleted The Sounds That Do Not Affect The Meaning Such As The Elision Of Some Vowels (Harakat) And When Removed, The Letter Is Pronounced With A Voweless Sound.In His Book, Sibawayh Explained That The Arabs Wanted To Ease Themselves When The Vowel (Haraka) Was Heavy On The Tongue Movement Because Of Its Proximity To Another Vowel. The Vowels That Are Deleted Are The Damma And Kasra, But The Fatha Is Not Deleted Because It Is Light.This Voice Principle - The Tendency Of The Speaker To Lightening - Corresponds To The Findings Of Modern Linguistics, Called The Linguistic Economy. Therefore, This Research Will Deal With Sibawayh’s Explanation In Deleting A Letter From The Word In The Light Of The Modern Voice Lesson. Key Words - Reason, Lightening, Elision Of Vowels (Harakat), Sibawayh's Book, Weight, Syllable.